Structure-property-performance relationship of vanadium- and manganese-based metal-organic frameworks and their derivatives for energy storage and conversion applications - Abazari, Reza; Sanati, Soheila; Nanjundan, Ashok Kumar; Wang, Qiyou; Dubal, Deepak P; Liu, Min (Journal of materials chemistry. A, Materials for energy and sustainability, 2024)
Energy crises are currently the main challenges for human life. Promising solutions are expected from research on novel materials with a wide range of functional benefits. The new family of materials, known as metal-organic frameworks (MOFs), with coordination bonds between a metal and organic matter as the center atom and ligand, respectively, are an exciting class of such functional materials. MOFs represent inorganic-organic hybrids of crystals, making them beneficial for different applications. In the past few years, several attempts have been made to modify pristine MOFs and achieve better characteristics, including a larger surface area, greater availability of active sites, highly stable materials, and improved transport and diffusion of mass. The present review summarizes MOFs containing vanadium and manganese, including multi-metallic materials, composites, and derivatives. It focuses on the structure, porosity, and stability and their impact on energy storage and conversion applications. Each MOF type containing vanadium and manganese is examined to highlight the association of porous structures and characteristics. This review will further provide a deep understanding and transparent insights into the functions of MOFs and their suitability for certain applications. Other interested researchers are recommended to examine material optimization and synthesis of various vanadium and manganese-based MOFs that are more stable while also showing higher capacity. Vanadium and manganese-MOFs have many different oxidation states that are useful for energy-related applications, and their comprehensive review in comparison with other first row transition metals has not been carried out yet. The current review discusses on vanadium- and manganese-based metal-organic frameworks and their derivatives for energy storage and conversion applications along with the potential future advancements in these fields.